Application Of K-Means Method In Grouping Horticultural Commodity Production Results In The Department Of Food Crops Horticulture And Plantations Of Bengkulu Province - Silola, Alun; Yupianti, Yupianti; Sudarsono, Aji (Jurnal Media Computer Science, 2025)
The Department of Agriculture, Food Crops, Horticulture and Plantations of Bengkulu Province is a government agency whose task is to collect data on horticultural commodities in the Bengkulu Province. In the Department of Agriculture, Food Crops, Horticulture and Plantations of Bengkulu Province, there is no specific system used to group data on horticultural commodity production results, so it is difficult to obtain information on horticultural commodities that fall into high, medium, and low production levels in Bengkulu Province. The application of the k-means method in grouping horticultural commodity production results at the Department of Food Crops, Horticulture and Plantations of Bengkulu Province can help the department obtain information on the results of grouping horticultural commodity data in Bengkulu Province, and can help determine planning programs and provide counseling to farmers in horticultural commodities, especially those in the low production group to increase their production results. Based on the data used in 2023 with 3 categories of horticultural commodities, the results of the grouping in the vegetable category cluster C1 were 3 commodities, cluster C2 was 9 commodities, cluster C3 was 13 commodities, in the fruit category cluster C1 was 4 commodities, cluster C2 was 7 commodities, cluster C3 was 20 commodities, in the medicinal plants and spices category cluster C1 was 2 commodities, cluster C2 was 1 commodity, cluster C3 was 13 commodities. In the vegetable horticultural commodity category that includes high production results are Large Chili (Group), Cabbage, Eggplant, the fruit horticultural commodity category that includes high production results is Durian, Orange (Group), Siamese Orange/Tangerine, Banana, and the vegetable horticultural commodity category that includes low production results is Ginger, Rhizome (Group).